MEDIAMORFOSIS OZ RADIO JAKARTA DALAM MEMBANGUN BUDAYA KOMUNIKASI DI ERA DIGITAL - Putera Aditya (2024)
The low number of users of radio media which is in third position with an interest level of 1.7% compared to the internet at 55.3% as the most popular media has encouraged the transformation of radio media in the digital era. The aim of this research is to determine the mediamorphosis of OZ Radio Jakarta in building a communication culture in the digital era. The research method used uses a qualitative ethnomethodological approach. The results of the research show firstly the application of OZ Radio Jakarta coevolution in the digital era in the form of digital language, secondly the application of OZ Radio Jakarta convergence using social media such as Instagram, TikTok, Twitter, and the website www.ozradiojakarta.com, and thirdly the application of complexity in media in OZ Radio changes in communication culture specialization. The research conclusion based on the results of interviews and observations shows that OZ radio has undergone a mediamorphosis from conventional radio to digital radio. Media transformation is carried out because of the complex relationship between felt needs and the development of technological innovation.